2014
DOI: 10.1002/pd.4485
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of first-trimester prevention for preeclampsia on anxiety

Abstract: A strategy of first-trimester screening for preeclampsia does not increase maternal anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…But by active engagement and alertness in their personal health, they expected the disadvantage of anxiety to be levelled out. Which is in line with findings of Simeone et al [25], who demonstrated that participating in a first-trimester preventive program for PE did not increase levels of anxiety [25]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…But by active engagement and alertness in their personal health, they expected the disadvantage of anxiety to be levelled out. Which is in line with findings of Simeone et al [25], who demonstrated that participating in a first-trimester preventive program for PE did not increase levels of anxiety [25]. …”
Section: Discussionsupporting
confidence: 92%
“…The results of our study suggest that the majority of women in this study had a positive attitude towards preeclampsia screening and were willing to participate when available, which is in line with earlier research regarding PE screening [24, 25]. When identified as high-risk, self-monitoring, together with increased alertness of healthcare professionals, was perceived as a means to take active actions to potentially improve pregnancy outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Whilst incorporation of PET screening into the combined first-trimester test presents some difficulties for counselling, expedience dictates this is both the most appropriate gestational point and cost-effective approach for screening [39]. There is no evidence that women defined as being at high risk for ePET have higher levels of anxiety later in their pregnancy [40].…”
Section: Prediction and Prevention Of Petmentioning
confidence: 98%
“…Furthermore, there is a concern about the long-term consequences of PE, as women who experience this disorder represent a high-risk group for subsequent premature cardiovascular, cerebrovascular, peripheral arterial diseases and other chronic illnesses later in life [19] [22] [29]- [33]. Early onset PE, which requires delivery before 34 weeks gestation is the clinical form that largely contributes to these increased risks [19]. Changes in PC noted in this study are in agreement with those reported by other researchers [9] [34]- [36].…”
Section: Discussionmentioning
confidence: 99%
“…[19]- [28]. Furthermore, there is a concern about the long-term consequences of PE, as women who experience this disorder represent a high-risk group for subsequent premature cardiovascular, cerebrovascular, peripheral arterial diseases and other chronic illnesses later in life [19] [22] [29]- [33].…”
Section: Discussionmentioning
confidence: 99%